Peningkatan Hasil Belajar Matematika dengan Menggunakan Lembar Kerja Siswa (LKS) dan Kartu Keaktifan Siswa (KKS) - Arfatin Nurrahmah; Ayi Mumuh Suhendar (Universitas Indraprasta PGRI, 2017)
Improving Mathematics Achievement through Students’ Work Sheet and students’ Card Creativity. The aim of this action research is to know the application of students? work sheet (LKS) and students? card creativity (KKS) on improving mathematics achievement. The research was conducted in class VII.1 in State Junior High School 280 Jakarta. This research was in three cycles, every cycle consist of four phase, they are planning, action, analysis, and fact finding about the result of the action. Analysis data was conducted through interview, questionair, and observation in the form of fields note. The process of data validation is done by triangulation techniques. Based on the result of the research, it can be concluded that, (1) Structured students? work sheet and giving score or value which is written in students? Card Creativity are able to make the learners more active and be independent in learning process; and (2) Learning through Students? work sheet (LKS) and students? Card Creativity (KKS) are able to improve students? mathematic achievement. It can be proven from mean value of students? mathematic achievement which increased from cycle I to cycle III. The mean value is increased from cycle I to cycle III, in cycle I is 73.67, in cycle II is 75.73 and in cycle III is 83.83.